Vermicomposting Of Palm Oil Mill Effluent (POME) Sludge And Effects Of Vermicompost On Oil Palm Seedling Growth - Bidattul Syirat , Zainal (2014)

(untitled)
The present study is about vermicomposting of palm oil mill effluent (POME) sludge as a low C/N ratio material and effects of vermicompost on oil palm seedling growth. Experiment on vermicomposting of low C/N ratio materials alone, without mixing, is very limited. There are limited literatures that have looked into this matter. Kajian ini adalah berkaitan tentang pengkomposan vermi bagi enapcemar efluen kilang minyak sawit dan kesan-kesan vermikompos ke atas pertumbuhan anak kelapa sawit. Eksperimen terhadap pengkomposan vermi hanya bagi bahan rendah nisbah C/N, tanpa percampuran, adalah sangat terhad. Hanya terdapat beberapa sumber sahaja yang meniliti kajian ini.